Intestinal stem cell-derived enteroids from morbidly obese patients preserve obesity-related phenotypes: Elevated glucose absorption and gluconeogenesis - Nesrin M. Hasan; Kelli F. Johnson; Jianyi Yin; Nicholas W. Baetz; Lea Fayad; Vadim Sherman; Sarah E. Blutt; Mary K. Estes; Vivek Kumbhari; Nicholas C. Zachos; Olga Kovbasnjuk (Elsevier, 2021)
Objective: The mechanisms behind the efficacy of bariatric surgery (BS) for treating obesity and type 2 diabetes, particularly with respect to the influence of the small bowel, remain poorly understood. In vitro and animal models are suboptimal with respect to their ability to replicate the human intestinal epithelium under conditions induced by obesity. Human enteroids have the potential to accelerate the development of less invasive anti-obesity therapeutics if they can recapitulate the pathophysiology of obesity. Our aim was to determine whether adult stem cell-derived enteroids preserve obesity-characteristic patient-specific abnormalities in carbohydrate absorption and metabolism. Methods: We established 24 enteroid lines representing 19 lean, overweight, or morbidly obese patients, including post-BS cases. Dietary glucose absorption and gluconeogenesis in enteroids were measured. The expression of carbohydrate transporters and gluconeogenic enzymes was assessed and a pharmacological approach was used to dissect the specific contribution of each transporter or enzyme to carbohydrate absorption and metabolism, respectively. Results: Four phenotypes representing the relationship between patients' BMI and intestinal dietary sugar absorption were found, suggesting that human enteroids retain obese patient phenotype heterogeneity. Intestinal glucose absorption and gluconeogenesis were significantly elevated in enteroids from a cohort of obese patients. Elevated glucose absorption was associated with increased expression of SGLT1 and GLUT2, whereas elevated gluconeogenesis was related to increased expression of GLUT5, PEPCK1, and G6Pase. Conclusions: Obesity phenotypes preserved in human enteroids provide a mechanistic link to aberrant dietary carbohydrate absorption and metabolism. Enteroids can be used as a preclinical platform to understand the pathophysiology of obesity, study the heterogeneity of obesity mechanisms, and identify novel therapeutics.